A Critical Analysis of Corporate Criminal Liability in Law Number 1 of 2023 - Samad, Rezki Purnama; Ardiansyah, Ardiansyah; Nabilah, Eva Albatun (CV. Social Politic Genius (SIGn), 2025)
Although the codification of corporate criminal liability in Law Number 1 of 2023 marks a paradigmatic advancement in Indonesian criminal law, its implementation is overshadowed by normative vulnerabilities that could undermine legal certainty. This research aims to critically analyze the architecture of corporate criminal liability, as regulated in Articles 45 through 50 of Law Number 1 of 2023, to identify its inherent conceptual and structural problems. Using a normative legal research method supported by statutory and conceptual approaches, as well as systematic interpretation techniques, this study dissects each layer of the norms that construct this liability mechanism. The findings indicate that Law Number 1 of 2023 has progressively expanded the definition of criminal law subjects and the scope of perpetrators to include beneficial owners, while also formulating pragmatic criteria for corporate fault. However, behind this progress, two fundamental problems were identified. First is the normative ambiguity arising from open-ended phrases such as “or that which is equated to it,” which risks creating disparities in judicial decisions. Second is a structural disharmony reflected in the functional redundancy between Articles 47 and 49 of Law Number 1 of 2023. It is concluded that the effectiveness of this entire corporate criminal liability framework will heavily depend on the active role of the judiciary as a law-finder (rechtsvinder) to clarify normative obscurities. Therefore, the issuance of technical guidelines by the Supreme Court is an urgent necessity to ensure consistent and just implementation.